Relationships between Interaction Energy and Electron Density Properties for Homo Halogen Bonds of the [(A)nY–X···X–Z(B)m] Type (X = Cl, Br, I) - Maxim L. Kuznetsov (Molecules, 2019)
Relationships between interaction energy (Eint) and electron density properties at the X···X bond critical point or the d(X···X) distance were established for the large set of structures [(A)nY−X···X−Z(B)m] bearing the halogen bonds Cl···Cl, Br···Br, and I···I (640 structures in total). The best estimator of Eint is the kinetic energy density (Gb), which reasonably approximates the whole set of the structures as −Eint = 0.128Gb2 − 0.82Gb + 1.66 (R2 = 0.91, mean absolute deviation 0.39 kcal/mol) and demonstrates low dispersion. The potential and kinetic energy densities, electron density, and the d(X···X) distance behave similarly as estimators of Eint for the individual series Cl···Cl, Br···Br, and I···I. A number of the Eint(property) correlations are recommended for the practical application in the express estimates of the strength of the homo-halogen bonds.